2003
DOI: 10.1002/cncr.11371
|View full text |Cite
|
Sign up to set email alerts
|

Adenosquamous histology predicts a poor outcome for patients with advanced‐stage, but not early‐stage, cervical carcinoma

Abstract: BACKGROUND The objective of this study was to compare survival between patients with adenocarcinoma and patients with adenosquamous carcinoma of the cervix. METHODS Patients who were diagnosed with invasive cervical carcinoma from 1988 to 1999 were identified from the Automated Central Tumor Registry for the United States Military Health Care System. Clinical data, including race, age at diagnosis, histology, tumor grade, disease stage, lymph node status, treatment modality, and survival, were collected. Survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
96
3
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 22 publications
(81 reference statements)
9
96
3
4
Order By: Relevance
“…Park et al found that the DFS and OS of patients with adenocarcinoma were significantly shorter than that of patients with squamous cell carcinoma (Park et al, 2010). Farley et al reported that the 5-year survival of patients with stage II -IV adenosquamous carcinoma was significantly lower than that of patients with adenocarcinoma of the same stage (Farley et al, 2003). Chen et al reported that the 5-year survival of patients with small cell carcinoma was significantly lower than that of patients with squamous cell carcinoma or adenocarcinoma (Chen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al found that the DFS and OS of patients with adenocarcinoma were significantly shorter than that of patients with squamous cell carcinoma (Park et al, 2010). Farley et al reported that the 5-year survival of patients with stage II -IV adenosquamous carcinoma was significantly lower than that of patients with adenocarcinoma of the same stage (Farley et al, 2003). Chen et al reported that the 5-year survival of patients with small cell carcinoma was significantly lower than that of patients with squamous cell carcinoma or adenocarcinoma (Chen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Following surgery, adenocarcinoma, adenosquamous carcinoma and small cell carcinoma need multimodality treatment with radiotherapy and chemotherapy (Farley et al, 2003;Chen et al, 2008;Park et al, 2010). It is believed that patients with stage Ⅰb-IIb non-squamous cell cervical cancer should be given comprehensive postoperative adjuvant therapy including radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although HR HPV is known to be pivotal in the development of cervical cancer, its role in cancer progression as assessed here for HPV16 against histological markers was found to be limited to an association with vascular involvement. HPV16 occurred more frequently in moderately differentiated cancers and did not show any preference for adenosquamous carcinoma, a histological type which is usually poorly differentiated and has a lower 5-year survival rate (Davy et al, 2003;Farley et al, 2003). In contrast, LOH in 3p was found to be associated with poor differentiation, increased depth of invasion and, when the LOH occurred in FHIT intron 3 with lymph node involvement or in FHIT intron 5 with abnormal FHIT protein expression (Table 3b).…”
Section: Discussionmentioning
confidence: 97%
“…The most common type of cervical cancer is squamous cell carcinoma (SCC) which comprises approximately 75% of all cervical cancers (Kosary, 1994;Farley et al, 2003).The second most common type is adenocarcinoma (ADC) accounting for about 20% (Wang et al, 2004). The remaining cases consist of rare histological types including small cell neuroendocrine carcinoma (SNEC) (Kosary, 1994;Farley et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining cases consist of rare histological types including small cell neuroendocrine carcinoma (SNEC) (Kosary, 1994;Farley et al, 2003). Over time, the rates of invasive SCC have declined, while the incidence of 5356 ADC (Smith et al, 2000;Wang et al, 2004;Mathew and George, 2009) and SNEC (Vinh-Hung et al, 2007) have increased.…”
Section: Introductionmentioning
confidence: 99%